Bargaining Foundations of Shapely Value - Gul, Faruk (Econometrica, 1989)
A transferable utility economy in which each agent holds a resource which can be used in combination with the resources of other agents to generate value (according to the characteristic function V) is studied using a dynamic model of bargaining. The main theorem establishes that the payoffs associated with efficient equilibria converge to the agents' Shapley values as the time between periods of the dynamic game goes to zero. In addition it is demonstrated that an efficient equilibrium exists and is unique when an additivity condition is satisfied. To demonstrate the sensitivity of the solution to the institutional detail we modify the model to allow for partnerships and show that the Shapley value is no longer achieved.